(3MGTjI chLcs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj,, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s
(3ChdgG (B:s
(3GdMeO ddg bhdg hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI Cbhd gcPG hLO YHGQI GdeJf aj cKjQ ef GdfSN hGdhGH Gf daX KdGK ggfG RjGOI hbYJ SghG ef bde GdfGSN jOd Ydi Pdc bhd (B...s
(3BNQgG (B:s
(3bGd haj chf GdehVhY LRAG ef GdYde Cbhd hbO CLjH Yf GdfXQ jefY GdMUQ hgh CfG dG fQjO jchf GdehVhY JUhQg LRA ef GdYde MJi jfOQL aj GdeHGOA GdJUhQjI hdG Cf GdJUOjb Hchfg ehVhYG ddYde (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\7s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs